Using Role Play Technique To Teach Speaking Skill Procedure Text In Tourism Department - Rusmawan, Putu Ngurah (IJET (Indonesian Journal of English Teaching), 2020)
In the revolution industry era 4.0, students in the tourism department need to be enabled to speak English fluently as an international language. The students need to improve their communication skills. Role play technique is one teaching technique that is applicable in the State Polytechnic of Banyuwangi because it focuses on practicing real-life communication skills. The researcher tried to investigate the teaching of speaking activities in the classroom. The study used descriptive qualitative research. The researcher analyzed and described the teaching speaking in procedure text by using role play technique for tourism department. The preparation of the lecturer included a syllabus and a learning contract, which contained teaching materials, the method, and learning sources. The process of teaching was divided into three steps they were pre-activity, main activity, and post-activity. He brought them in class. The lecturer used role play technique. The lecturer only facilitated the students to be motivated in learning the speaking procedure text. He asked the students to do a simulation communication in a hotel. One of the students plays the role of a receptionist and the other as a customer. During the teaching and learning process, the lecturer faced three main troubles in conducting the teaching process. The students were’ low in vocabulary, pronunciation, and had difficulty expressing sentences, and the lecturer provided the solution. Speaking procedure text course, which was taught by the lecturer, proceeded effectively and was acceptable to the students.